OC-127 One thousand laparoscopic ROUX-EN-Y gastric bypasses: perioperative and long term outcomes. (28th May 2012) - Tham, J C; Pournaras, D; Finlay, I; Titcomb, D; Edmond, J; Mahon, D; Welbourn, R
Abstract : Introduction: Laparoscopic Roux-en-y gastric bypass (LRYGB) has been established as an effective treatment for obesity and obesity related morbidity. However, safety of LRYGB remains under public scrutiny. Defining operative outcomes is vital to establish its safety and long term efficacy. Methods: One thousand consecutive patients underwent LRYGB as a primary procedure by two surgeons in a single centre from 2004 to 2011. Twenty-six patients had intra-gastric balloon insertion before LRYGB to reduce Body Mass Index (BMI). LRYGB was done using a retrocolic, antegastric linear staple technique with routine closure of internal hernia defects. Patient demographics and complications were collected prospectively in a local database, and after January 2009, in the National Bariatric Surgery Registry. The Obesity Surgery Mortality Risk Score (OS-MRS) was used for risk stratification. Analysis was performed on each 100 patients making up 10 groups sequentially with the first 100 in group 1. Results: Mean age±SD was 45.5±10.4 with mean BMI of 49.5±7.7 and 79.3% were female. There were 61 (6.1%) high-risk patients (OS-MRS class C). The follow-up rate up to 6 years was 87.9%. There were four conversions-to-open surgery in the first 400 patients with no conversions thereafter. Mean % excess weight loss (EWL) pre-operatively as compared to initial weight was 11.6%±12.5. % EWL subsequently was: 1 year 67.7%±18.9; 2 years: 71.6%±20.3; 5 years: 57.5%±21.8; 6 years: 61.1%±21.4. Overall, the 30-day complication rate was 5.5% with a 30-day reoperation rate of 2.9%. The 30-day complication rate fell over time; 13 patients had a complication in group 1 compared to 1 patient in group 10 (p=0.03). Further, there was significant reduction in complications between groups 1 and 2 (p<0.001) but no difference between each group thereafter. Major complications within 30 days postoperatively were gastrointestinal leak (0.6%), gastro-jejunal stenosis (0.3%), stenosis at the mesocolic defect (0.3%), jejuno-jejunostomy hernia (0.7%), mesocolic hernia (1%) and bleeding (2.1%). There was one death (0.1%) within the 30 postoperative days (in group 2). The cumulative complication rate at 6 years was 9.1% with 5.8% needing re-operation or endoscopic intervention. The mean operative time per group for the first 600 patients was, in minutes, 163±53.7, 129.2±109.8, 100.0±27.8, 104.3±28.9, 92.7±32.1 and 93.8±30.9, a significant decrease between groups 1 and 2 (p=0.003), 2 and 3 (p=0.007), and 4 and 5 (p=0.008) respectively, but not between 3 and 4. Conclusion: LRYGB is a safe and efficacious procedure with sustained weight loss at 6 years. The learning curve is about 100 cases but operative time continues to improve up to the 500th case. A high volume centre is associated with low morbidity and mortality. Competing interests: None declared.